PENYELIDIKAN OPERASI PINTU INTAKE EMBUNG SAMIRAN DENGAN UJI MODEL HIDROLIK - Dwi Kurniani; Kirno Kirno (Diponegoro University, 2010)
A manual of intake gate operation for embung is an important tool it depends. One factor which is decidingthe manual is operation of gate system. If the system of gate operation of intake gate are wrong will havenegative water use . To make the most precise of manual operation of intake gate embung Samiran must beendone physical model test. From this test result of physical model test can be used as a guidance or referenceprototype application.